Redescription of ingliseria cirrohamata (Linstow, 1888) (Nematoda: Acuariidae), including new hosts and geographical records - Diaz, Julia Inés; Fonteneau, Frédéric; Panisse, Guillermo; Cremonte, Florencia; Navone, Graciela Teresa (Journal of Parasitology)
Inglisera cirrohamata (Linstow, 1888) (Nematoda: Acuariidae) is redescribed based on specimens collected from the type host, Phalacrocorax verrucosus (Aves: Phalacrocoracidae), and the type locality, Kerguelen Island, in the southern Indian Ocean. Three new hosts and 2 new localities were recorded, i.e., Phalacrocorax atriceps albiventer and P. brasilianus from Puerto Madryn, Argentina and P. magellanicus from Puerto Williams, Chile. The structure of the cephalic ornamentations was observed and fully described. The presence of 6 pairs of postcloacal papillae is confirmed, a description of the tip of left spicule is given, and the presence of post-deirids is reported for the first time. This constitutes the first record of this nematode in South America and provides the first study of the genus by scanning electron microscopy. Fil: Diaz, Julia Inés. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Estudios Parasitológicos y de Vectores. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Centro de Estudios Parasitológicos y de Vectores; Argentina Fil: Fonteneau, Frédéric. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Estudios Parasitológicos y de Vectores. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Centro de Estudios Parasitológicos y de Vectores; Argentina Fil: Panisse, Guillermo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Estudios Parasitológicos y de Vectores. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Centro de Estudios Parasitológicos y de Vectores; Argentina Fil: Cremonte, Florencia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Estudios Parasitológicos y de Vectores. Universidad Nacional de La Plata. Facultad de Ciencias ...